Implications of the Influence of Corporate Financial Performance on Sukuk Ijarah in the Development of Indonesian Sharia Finance - Handayani, Meutia; Ramadhan, Rizki; Farlian, Talbani (STMIK Widya Cipta Dharma, 2024)
In this study, the purpose is to analyze the influence of Islamic financial capabilities, particularly focusing on performance metrics such as profitability, current liabilities, and leverage, on sukuk ijarah issuance by corporations during the observation period from 2018 to 2024 in Indonesia. The sample consists of all companies registered with the Financial Services Authority (OJK) that issue sukuk under the sukuk ijarah scheme. The study evaluates the companies' performance in terms of their ability to generate profitability, finance short-term debts arising from sukuk ijarah issuance, and meet long-term obligations when the sukuk mature. This study employs multiple regression analysis using the Eviews 11 software. The results indicate that profitability, liquidity, and leverage, both individually and collectively, significantly affect sukuk ijarah performance. Furthermore, companies issuing sukuk ijarah during the research period demonstrate that sukuk ijarah can enhance profitability. Additionally, these companies exhibit the ability to meet both short-term and long-term debt obligations, ensuring the repayment of underlying assets tied to the issued sukuk ijarah.